Changes in the adjustment processes of fresh-year students in the conditions of military actions in Ukraine - Sas Леся (Psychosomatic Medicine and General Practice, 2022)
These graphic materials are a poster presentation for the III Congress with international participation "PSYCHOSOMATIC MEDICINE OF THE XXI CENTURY: REALITIES AND PERSPECTIVES". Which took place on November 4-6, 2022 in Kyiv on the Mediamed portal.